2016
DOI: 10.1016/j.icarus.2015.11.023
|View full text |Cite
|
Sign up to set email alerts
|

Asteroid (21) Lutetia: Disk-resolved photometric analysis of Baetica region

Abstract: ABSTRACT. (21) Lutetia has been visited by Rosetta mission on July 2010 and observed with a phase angle ranging from 0.15 to 156.8 degrees. The Baetica region, located at the north pole has been extensively observed by OSIRIS cameras system. Baetica encompass a region called North Pole Crater Cluster (NPCC), shows a cluster of superposed craters which presents signs of variegation at the small phase angle images. For studying the location, we used 187 images distributed throughout 14 filter recorded by the NAC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(54 citation statements)
references
References 77 publications
(105 reference statements)
3
50
1
Order By: Relevance
“…The high value of P indicates a very porous surface and can be considered as an upper limit, given that according to Hapke's treatment of SHOE, a real grain size distribution which is not monodisperse can provide a similar OE peak for larger values of φ. High values of porosity inferred from Hapke's modeling are not uncommon for planetary surfaces (Domingue et al 2002;Hapke & Sato 2016;Hasselmann et al 2017). This result, at least from a qualitative point of view, is in good agreement with the low thermal inertia of Ceres, as derived from both ground-based observations (Müller & Lagerros 1998;Chamberlain et al 2009) and recent analysis of VIR data (Rognini et al 2019), which may be compatible with a highly porous regolith.…”
Section: Angular Width Of the Opposition Effect And Regolith Porositysupporting
confidence: 85%
See 1 more Smart Citation
“…The high value of P indicates a very porous surface and can be considered as an upper limit, given that according to Hapke's treatment of SHOE, a real grain size distribution which is not monodisperse can provide a similar OE peak for larger values of φ. High values of porosity inferred from Hapke's modeling are not uncommon for planetary surfaces (Domingue et al 2002;Hapke & Sato 2016;Hasselmann et al 2017). This result, at least from a qualitative point of view, is in good agreement with the low thermal inertia of Ceres, as derived from both ground-based observations (Müller & Lagerros 1998;Chamberlain et al 2009) and recent analysis of VIR data (Rognini et al 2019), which may be compatible with a highly porous regolith.…”
Section: Angular Width Of the Opposition Effect And Regolith Porositysupporting
confidence: 85%
“…Following the end of the nominal mission (18 June 2016), Dawn operations went through a series of extensions, and on 29 April 2017, during the Extended Mission Orbit 4 (XMO4), a dedicated maneuver allowed the imaging instruments to observe Ceres at opposition, thus exploring the low-phase-angle part of the phase curve, which until that time had only been investigated by ground-based observations (Tedesco et al 1989;Reddy et al 2015), and where a phenomenon known as the opposition effect (OE) takes place. The OE is a surge in reflectance commonly observed in particulate media at small phase angles (Hapke 2012), and has been widely observed on atmosphereless bodies of the Solar System, such as the Moon (Buratti et al 1996;Helfenstein et al 1997;Shkuratov et al 1999), asteroids (Belskaya & Shevchenko 2000;Domingue et al 2002;Kitazato et al 2008;Spjuth et al 2012;Masoumzadeh et al 2015;Shevchenko et al 2016), comets (Ciarniello et al 2015;Hasselmann et al 2017), icy moons (Helfenstein et al 1998;Pitman et al 2010;Ciarniello et al 2011), and rings (Déau et al 2013;Salo & French 2010), as well as in laboratory measurements (Nelson et al 2000;Jost et al 2017). Two mechanisms are proposed as the main contributors to this effect: the shadow hiding OE (SHOE) and the coherent backscattering OE (CBOE).…”
Section: Introductionmentioning
confidence: 99%
“…16, the two models for Lutetia results in the same SPPF at phase angles less than about 60º, then starts to diverge towards higher phase angles. Hasselmann et al (2016) analyzed the Baetica region on Lutetia and found an overall consistent but slightly more backscattering results in its photometric properties than the global average. (4) Vesta (Li et al 2013) could be modeled with a 1pHG without systematic bias.…”
Section: Forward Scatteringmentioning
confidence: 94%
“…For the asteroid Lutetia, we found two sources for the Minnaert parameter in the literature. Masoumzadeh et al (2015) found c M to drop off at higher phase angle, but the linear relation of Hasselmann et al (2016) shows the familiar increase.…”
Section: Clear Filtermentioning
confidence: 96%